Benak Dress Avantgarde Categories - Mohamad Faizuan, Bin Mat (Saradise Gallery, 2019)
Benak Dress is a collaborative effort by the painter (Mohamad Faizuan Mat) and designer (Aizat Rahman) to produce a masterpiece (dress). The dress was showcased during RIMBA Fashion Art Show at Saradise Gallery, Kuching Sarawak.